2014
DOI: 10.1002/dvg.22767
|View full text |Cite
|
Sign up to set email alerts
|

The Zic2 gene directs the formation and function of node cilia to control cardiac situs

Abstract: Summary: The first molecular herald of organ asymmetry during murine embryogenesis is found at the periphery of the node in early-somite stage embryos. Asymmetric gene expression and calcium accumulation at the node occurs in response to a left-ward flow of extracellular fluid across the node, generated by motile cilia within the pit of the node and likely sensed by immotile cilia in the periphery of the node. The ciliation of node cells is controlled by a cascade of node-restricted transcription factor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
12
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 54 publications
7
12
2
Order By: Relevance
“…This hypothesis is supported by the partial rescue of coloboma by Hh inhibition in MZ-zic2 mutants. Notably, mouse zic2 promotes formation of the embryonic organizer during gastrulation (Barratt et al, 2014; Houtmeyers et al, 2016; Warr et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the partial rescue of coloboma by Hh inhibition in MZ-zic2 mutants. Notably, mouse zic2 promotes formation of the embryonic organizer during gastrulation (Barratt et al, 2014; Houtmeyers et al, 2016; Warr et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…HPE is best understood as a conserved sequence of developmental steps that begin in the early gastrulating embryo (Arnold & Robertson, 2009). Driver genes are inextricably linked to this developmental sequence, beginning with TGF-signals around the node (Barratt, Glanville-Jones, & Arkell, 2014;Beddington & Robertson, 1999;Houtmeyers et al, 2016;Powers et al, 2010;Robertson, 2014;Warr et al, 2008), the establishment of the primitive streak and its midline progenitors (Herion, Salbaum, & Kappen, 2014), the precise positioning of the prechordal plate beneath the midline neuro-ectoderm (England, Blanchard, Mahadevan, & Adams, 2006), the activation of midline hedgehog signals (Geng et al, 2008;Jeong et al, 2008;Ohkubo, Chiang, & Rubenstein, 2002;Okada, Okumura, Motoyama, & Ogawa, 2008), and/or cooperating with them in the forebrain (Carlin et al, 2012;Gestri et al, 2005;Geng, Acosta, Lagutin, Gil, & Oliver, 2016;Lavado, Lagutin, & Oliver, 2008;Lee et al, 2017;Storm et al, 2006).…”
mentioning
confidence: 99%
“…Studies in mutant mice showed that HPE is produced by a transient defect in the development of prechordal plate, a structure required for forebrain midline morphogenesis, validating the function of Zic2 during organizer formation . The Zic2 null mice have cardiac situs problems, indicating a L‐R axis patterning defect . By examining the embryos at later stages, more cardiovascular malformations have been found, such as abnormal ventricular topology, great artery transposition, double outlet right ventricle, ventricular septal defect, and rightward looped aortic arch .…”
Section: Discussionmentioning
confidence: 93%